Improving Quality of Care and Patient Safety Through Morbidity and Mortality Conferences. Issue 1 (24th April 2012) - Bal, Gaëlle; Sellier, Elodie; Tchouda, Sandra D.; François, Patrice
Abstract The objective was to evaluate the analysis of adverse events and the decisions for quality improvement decided during morbidity and mortality conferences (MMCs). We conducted a prospective observational study of MMCs conducted in a teaching hospital between November 2007 and May 2008. Two observers attended the conferences and collected data on the structure of MMCs, the discussion between attendees, and the decisions or actions for quality improvement. Twenty‐four MMCs were studied including 146 cases. A majority of the senior physicians present (87.7%) took part in debating the cases; the participation of residents was lower (32.6%) and varied between departments (p < .001). Few paramedical professionals and other attendees participated in the debate. Shortcomings were sought in 91% of cases, but a structured method was used in less than 10% of cases. An analysis of underlying factors contributing to these shortcomings was observed in 75% of cases, with 4% considered structured and thorough. Eighty‐five decisions or actions to improve quality of care or patient safety were listed, with 28 of them (33%) planned for implementation. Discussion of adverse events appears to lack a structured method and although a large number of decisions for quality improvement were declared, fewer actions were planned with a timeline.